Earth pressure distribution in a braced excavation - Lim, Vuthy (2017)
Apparent Pressure Diagram (APD) was used in many strutting system designs in the past. It provides good conservative estimate of pressure but not for economical designs. Finite Element Analysis (FEA) software packages are commonly used nowadays to produce more accurate result. In this parametric study, excavation in soft clay overlaying medium clay was simulated in staged construction using FEA software, Plaxis 2D, under plane strain analysis. Mohr-Coulomb with linearly elastic-perfectly plastic material model was used with 3 types of undrained shear strength increasing with depth. Three sheet pile walls and diaphragm walls were also used as parameter. Result of this study found factor of safety to be minimum 3.25 and maximum 3.75 for all cases studied. Compared with FEA, APD overestimates strut force by 2.2 times for the case with least strut force and 2.0 times for the most strut force. Reduction in soil-wall interface strength leads to higher strut loads, deflection and bending moment. Prestressing strut results in even more strut loads, which lowers factor of safety against APD to approximately 1.46.